(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Gridhrasi comes under 80 types of Nanatmaja Vatavyadhi. The cardinal signs and symptoms of Gridhrasi are Ruk (pain), Toda (pricking sensation), Spandana (twitching) in the Sphik, Kati, Uru, Janu, Jangha and Pada in order and Sakthikshepa Nigraha i.e., restricted lifting of the leg associated with Gourava, Aruchi. Kati Basti is widely being practiced throughout country as Bahyaupakrama which has both Snehana and Swedana effects. Matra Basti is Snehana procedure which does Vataanulomana, Vatashamana. Objectives: To evaluate the efficacy of Matrabasti and Katibasti with Dhanvantaram Taila in the management of Gridhrasi. Materials and Methods: Patients presenting with the classical features of Gridhrasi and between the age group of 16 to 50 years irrespective of sex were selected and allotted in Group A, B and C with 15 patients in each group. Group A was administered with Matra basti with Dhanwantram Taila and Group B with Kati basti with Dhanwantram Taila and Group C with both Matra basti and Kati basti with Dhanwantram Taila for 9 days. Results: In combined treatment of Kati Basti and Matra Basti in Group C there was tremendous response in relieving Ruk (73%), Toda (46%), Spandana (60%), Supti (80%), Gourava (73%), Aruchi (66%), Sparshasahyata (73.3%) SLR (60%). In Group A, patients subjected to Matra Basti was effective in relieving Ruk (26.7%), Toda (13.3%), Spandana (26.7%), Supti (66.7%), Gourava (46.7%), Aruchi (53.3%), Sparshasahyata (13.3%) SLR (6.7%). In Group B patients subjected to Kati Basti was effective in relieving Ruk (6.7%), Toda (0%), Spandana (0%), Supti (40%), Gourava (20%), Aruchi (0%), Sparshasahyata (20%) SLR (0%). Conclusion: On the basis of the results of this study, it can be clearly concluded that combined treatment of Matrabasti and Kati basti with Dhanwantaram taila provided significant relief in the signs and symptoms of Gridhrasi than individually performed Matra basti and Kati basti with Dhanwantaram taila.